Phase 1 repolarization rate defines Ca2+ dynamics and contractility on intact mouse hearts - López Alarcón, María Micaela (2019)
In the heart, Ca2+ influx through L-type Ca2+ channels triggers Ca2+ release from the sarcoplasmic reticulum. In most mammals, this influx occurs during the ventricular action potential (AP) plateau phase 2. However, in murine models, the influx through L-type Ca2+ channels happens in early repolarizing phase 1. The aim of this work is to assess if changes in the open probability of 4-aminopyridine (4-AP)–sensitive Kv channels defining the outward K+ current during phase 1 can modulate Ca2+ currents, Ca2+ transients, and systolic pressure during the cardiac cycle in intact perfused beating hearts. Pulsed local-field fluorescence microscopy and loose-patch photolysis were used to test the hypothesis that a decrease in a transient K+ current (Ito) will enhance Ca2+ influx and promote a larger Ca2+ transient. Simultaneous recordings of Ca2+ transients and APs by pulsed local-field fluorescence microscopy and loose-patch photolysis showed that a reduction in the phase 1 repolarization rate increases the amplitude of Ca2+ transients due to an increase in Ca2+ influx through L-type Ca2+ channels. Moreover, 4-AP induced an increase in the time required for AP to reach 30% repolarization, and the amplitude of Ca2+ transients was larger in epicardium than endocardium. On the other hand, the activation of Ito with NS5806 resulted in a reduction of Ca2+ current amplitude that led to a reduction of the amplitude of Ca2+ transients. Finally, the 4-AP effect on AP phase 1 was significantly smaller when the L-type Ca2+ current was partially blocked with nifedipine, indicating that the phase 1 rate of repolarization is defined by the competition between an outward K+ current and an inward Ca2+ current.